Biometrics and body masses of some birds of prey of Argentina - Aráoz, Rodrigo (2016)
We present data from 97 live specimens from 20 different taxa of diurnal raptors from Argentina. Data were obtained from bird banding campaigns conducted by the Centro Nacional de Anillado de Aves (CENAA), Universidad Nacional de Tucumán, Argentina. Another important source of data was the Centro de Rehabilitación de Aves Rapaces (CeRAR). We used mist nets and balchatri traps to catch birds during CENAA campaigns in central and northern Argentina, in order to band them and study their migration. During fieldwork, we measured total body length, bill length (exposed culmen and culmen with cere), wing chord, and body mass of each bird. The biometric information of raptors in Argentina is scarce. These measurements can therefore be useful for a variety of topics such as conservation, ecology, biology, taxonomy and phylogeny.